2020
DOI: 10.1002/jsfa.10699
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the oxidation of pork fat by illumination and fat oil for the production of Baijiu beverage

Abstract: BACKGROUNDAged pork fat, deeply oxidized pork fat soaked in basic liquor for more than half a year, is an important material in producing Chi‐aroma Baijiu (CAB). With the expansion of production scale of CAB, innovative strategies for efficient production of aged pork fat are in great demand. The purpose of this study is to accelerate the lipid oxidation of pork fat and improve the productivity of aged pork fat.RESULTSResults showed that polyunsaturated fatty acids (PUFAs) were the main reactant; generation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
1
2
Order By: Relevance
“…The contents of UFA in lipid extracted from PFP treated by T2 and T3 were 22.39% and 10.88% higher than that by T1, which was consistent with studies that the content of UFA in pork fat with illumination (high oxidation level) was higher than those in the control (Wei et al., 2021), and the content of polyunsaturated fatty acids (PUFA) of carp liver in hyperoxia was higher than that in anoxia (Radi et al., 1988). The highest SFA and UFA in all groups of PFP were C16:0 and C18:1, which were consistent with household stir‐frying mutton sao zi (Bai et al., 2021).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The contents of UFA in lipid extracted from PFP treated by T2 and T3 were 22.39% and 10.88% higher than that by T1, which was consistent with studies that the content of UFA in pork fat with illumination (high oxidation level) was higher than those in the control (Wei et al., 2021), and the content of polyunsaturated fatty acids (PUFA) of carp liver in hyperoxia was higher than that in anoxia (Radi et al., 1988). The highest SFA and UFA in all groups of PFP were C16:0 and C18:1, which were consistent with household stir‐frying mutton sao zi (Bai et al., 2021).…”
Section: Resultssupporting
confidence: 90%
“…The results showed that the PV of PFP in T2, T3, and T4 conditions was 41.96‐, 16.70‐ and 14.20‐fold higher and the p‐AnV was 27.13‐, 6.94‐ and 6.70 fold higher than that in T1 (only lipase pretreatment), respectively. The p‐AnV of PFP treated by T2–T4 was more than 10 and was higher than the reported result (Wei et al., 2020, 2021). So, T2 conditions had the best effect on promoting lipid oxidation for PV and p‐AnV.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…[ 16 ] The AV and peroxide value (POV) of oil samples were determined according to GB 5009.229—2016 and GB 5009.227—2016, respectively, as described by Wei et al. [ 17 ] Briefly, for AV, 20 g oil was titrated with 0.1 mol L −1 KOH standard solution and AV was expressed as KOH in mg g −1 of oil. The 2 g oil was titrated with 0.01 mol L −1 sodium thiosulfate standard solution and POV was expressed as reactive oxygen in mmol kg −1 of oil.…”
Section: Methodsmentioning
confidence: 99%